2006
DOI: 10.1242/jcs.03198
|View full text |Cite
|
Sign up to set email alerts
|

Targeted homozygous deletion of M-band titin in cardiomyocytes prevents sarcomere formation

Abstract: Titin, a multifunctional protein that stretches from the Z-disk to the M-band in heart and skeletal muscle, contains a kinase domain, phosphorylation sites and multiple binding sites for structural and signalling proteins in the M-band. To determine whether this region is crucial for normal sarcomere development, we created mouse embryonic stem cell (ES) lines in which either one or both alleles contained a targeted deletion of the entire M-band-coding region, leaving Z-disk-binding and myosin-filament-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…The deletion of the M-band region of titin resulted in significant impairment of sarcomere assembly in cardiomyocytes derived from embryonic stem cells (Musa et al 2006). Similar abnormalities of myofibrillogenesis have been reported in titin M-line deficient mice (Peng et al 2005;Weinert et al 2006) and in mouse skeletal myotubes that differentiated in culture following titin truncation (Miller et al 2003).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The deletion of the M-band region of titin resulted in significant impairment of sarcomere assembly in cardiomyocytes derived from embryonic stem cells (Musa et al 2006). Similar abnormalities of myofibrillogenesis have been reported in titin M-line deficient mice (Peng et al 2005;Weinert et al 2006) and in mouse skeletal myotubes that differentiated in culture following titin truncation (Miller et al 2003).…”
Section: Discussionsupporting
confidence: 59%
“…This is consistent with the localization of these proteins at different sarcomeric compartments and their signaling properties in addition to the structural involvement in the process of myofibril assembly. Of special interest is the fact that functional impairment of obscurin expression in cardiac ) and skeletal muscle ) results in similar effects on the structure of the contractile apparatus as the down-regulation of titin function (Person et al 2000;Musa et al 2006;Seeley et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of C-terminal phosphorylatable residues may disrupt a regulatory function; earlier in vitro studies indicated that human S157 is phosphorylated by the titin kinase (TK) domain (Valle et al, 1997;Mayans et al, 1998). This mechanism may be relevant in vivo, as deletion of M-line titin, including the TK domain, disrupts myofibrillogenesis and results in mistargeting of telethonin (Miller et al, 2003;Musa et al, 2006). Alternatively, structural analysis of fulllength human telethonin in complex with titin by X-ray crystallography, small-angle X-ray scattering, and circular dichroism suggest the C-terminal is possibly involved in dimeric or higher order assembly of titin-telethonin complexes .…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…We next examined myoseverin treatment on the localization of titin, the largest described protein in the cell that spans from the M-band to the Z-disk and is required for sarcomere formation [Musa et al, 2006;Weinert et al, 2006]. We utilized an antibody that specifically recognized an epitope (T11) on the A-I junction region of the titin molecule [Furst et al, 1988].…”
Section: Characterization Of Myoseverin Disrupted Myofibrils With Sarmentioning
confidence: 99%